The contemporary management and coronary angioplasty outcomes in young patients with ST-Elevation myocardial infarction (STEMI) age < 40 years old: the insight from nationwide Thai PCI registry - Pornwalee Porapakkham; Pramote Porapakkham; Suphot Srimahachota; Thosaphol Limpijankit; Songsak Kiatchoosakun; Mann Chandavimol; Anek Kanoksilp; Thamarath Chantadansuwan; Ammarin Thakkinstian; Nakarin Sansanayudh (BMC Cardiovascular Disorders, 2024)
Abstract Background Cardiovascular disease (CVD) remains one of the major causes of death around the world in which ST elevation MI (STEMI) is in the lead. Although the mortality rate from STEMI seems to decline, this result might not be demonstrated in young adults who basically have different baseline characteristics and outcomes compared with older patients. Methods Data of the STEMI patients aged 18 years or older who underwent PCI during May 2018 to August 2019 from Thai PCI Registry, a prospective, multi-center, nationwide study, was included and aimed to investigate the predisposing factors and short-term outcomes of patients aged < 40 years compared with age 41–60, and > 61 years. Results Data of 5,479 STEMI patients were collected. The patients’ mean age was 62.6 (SD = 12.6) years, and 73.6% were males. There were 204, 2,154, and 3,121 patients in the youngest, middle, and oldest groups. The young patients were mainly male gender (89.2% vs. 82.4% and 66.6%; p < 0.001), were current smokers (70.6%, 57.7%, 34.1%; p < 0.001), had BMI ≥ 25 kg/m2 more frequently (60.8%, 44.1%, 26.1%; p < 0.001), and had greater family history of premature CAD (6.9%, 7.2%, 2.9%; p < 0.001). The diseased vessel in the young STEMI patients was more often single vessel disease with the highest percentage of proximal LAD stenosis involvement. Interestingly, there were trends of higher events of procedural failure (2.9%, 2.1%, 3.3%; p = 0.028) and procedural complications (8.8%, 5.8%, 9.4%; p < 0.001) in both youngest and oldest groups compared to the middle-aged group. In-hospital death was found in 3.4% in the youngest group compared to 3.3% in the middle-aged patients and 9.2% in the older patients (p < 0.001). Conclusions Despite experiencing higher rates of procedural failure and complications during treatment compared to middle-aged and older patients, young STEMI individuals demonstrate a significantly lower risk of death during hospitalization and within one year of the event. Younger patients might have a more robust physiological reserve or benefit from more aggressive post-procedure management. However, the higher prevalence of modifiable risk factors like smoking and obesity in younger individuals underscores the need for preventative measures. Encouraging smoking cessation and weight control in this demographic is crucial not only to prevent STEMI but also to potentially improve their long-term survival prospects.